2015
DOI: 10.1063/1.4936962
|View full text |Cite
|
Sign up to set email alerts
|

Coherent vertical electron transport and interface roughness effects in AlGaN/GaN intersubband devices

Abstract: We investigate electron transport in epitaxially grown nitride-based resonant tunneling diodes (RTDs) and superlattice sequential tunneling devices. A density-matrix model is developed, and shown to reproduce the experimentally measured features of the current-voltage curves, with its dephasing terms calculated from semi-classical scattering rates. Lifetime broadening effects are shown to have a significant influence in the experimental data. Additionally, it is shown that the interface roughness geometry has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
(74 reference statements)
2
21
0
Order By: Relevance
“…Transfer matrix calculations by Sakr et al showed the connection between the strong polarization fields and the asymmetric I-V characteristics [44]. More recently, after repeatable III-nitride RTD behavior was achieved, the focus was mainly on the forward bias resonance [25][26][27]29]. It should be noted, however, that the internal polarization fields markedly manifest also in the reverse bias regime giving rise to a characteristic threshold voltage V th given by Eq.…”
Section: Polar Rtd Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer matrix calculations by Sakr et al showed the connection between the strong polarization fields and the asymmetric I-V characteristics [44]. More recently, after repeatable III-nitride RTD behavior was achieved, the focus was mainly on the forward bias resonance [25][26][27]29]. It should be noted, however, that the internal polarization fields markedly manifest also in the reverse bias regime giving rise to a characteristic threshold voltage V th given by Eq.…”
Section: Polar Rtd Modelmentioning
confidence: 99%
“…More recently, III-nitride RTDs with low Al-composition AlGaN barriers have also been studied at cryogenic temperatures [25][26][27]. These devices, grown on freestanding GaN substrates (with low dislocation densities ∼5 × 10 6 cm −2 ), feature small mesa areas of ∼16 μm 2 aimed towards minimizing the number of defects per device.…”
Section: Introductionmentioning
confidence: 99%
“…3) Contact resistance parameter can significantly shift V -I characteristics, and approximate values can be obtained experimentally. Typical values are several ohms [39]. For the device in Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Resonant tunnelling diodes (RTDs) are interesting devices in their own right, and also the simplest devices in which vertical tunneling and scattering transport can be extensively investigated, both experimentally and theoretically: the experience might then be transferred to the design of more complicated, optoelectronic devices. With these aims we have investigated electron transport in epitaxially grown nitridebased resonant tunneling diodes (RTDs), as well as in superlattice-type sequential tunneling devices [3]. The density-matrix model was developed, and shown to be able to reproduce the experimentally measured current-voltage characteristics, with the dephasing terms in the model calculated from semi-classical scattering rates.…”
Section: Design Considerations For Gan/aln Based Unipolar (Opto-)elecmentioning
confidence: 99%